মুক্ত গণতন্ত্র রদ্ধ রাজনীতি : বাংলাদেশ ১৯৯১-২০১৭ - রহমান, মতিউর (ঢাকা : প্রথমা প্রকাশন, 2018)
Articles on contemporary political issues of Bangladesh.
Residential Campus
GenEd (Residential Campus)
Development Book Agency
In Bengali.
Keywords: Politics and government; Bangladesh -- Politics and government -- 1971-; Bangladesh